SCHOOL AND PARENT COLLABORATION TO SUPPORT EARLY CHILDHOOD LIFE SKILLS - Esafitri, Ameilina; Santoso, Sandy Tegariyani Putri; Mukhlis, Akhmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The Purpose of this study is to (1) find out the form of teacher and parent collaboration in building early childhood life skills, (2) find out what factors influence teacher and parent collaboration in building early childhood life skills. (3) knowing the development of life skills that are built through collaboration between teachers and parents. The research method used in this research is qualitative research with a case study approach. The subjects involved in the research were parents of students who took part in school activities and children aged 4-6 years, totaling 8 in Kindergarten A and Kindergarten B. Researchers collected data using observation, interview and documentation techniques. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The results of the research showed that (1) the forms of collaboration between teachers and parents at school are parenting, communication, home visits, learning at home (2) the influencing factors are time, parents' views of teachers, understanding of cooperation, parents' self-confidence. (3) teacher and parents collaboration supported the early childhood Life Skills